2001
DOI: 10.1093/ajcn/73.2.246
|View full text |Cite
|
Sign up to set email alerts
|

Calcium supplementation of chocolate: effect on cocoa butter digestibility and blood lipids in humans

Abstract: Calcium supplementation can be used as a means of reducing the absorbable energy value of chocolate. Supplementation with 2.25% CaCO3 had no effect on the taste of chocolate, was well tolerated by the subjects, and reduced LDL cholesterol in a short-term study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
103
6
6

Year Published

2004
2004
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 120 publications
(121 citation statements)
references
References 19 publications
6
103
6
6
Order By: Relevance
“…The non-significant change in total cholesterol in the calcium supplement group is in parallel with other findings (Karanja et al, 1987;Bell et al, 1992;Bostick et al, 2000;Entezari et al, 2001;Shahkhalili et al, 2001;Reid et al, 2002) except that reported by Denke et al (1993). Noting that this report suffers from weak points with regard to the number of participants, large amount of calcium supplemented and specific population investigated, more studies are still needed for a consistent conclusion.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…The non-significant change in total cholesterol in the calcium supplement group is in parallel with other findings (Karanja et al, 1987;Bell et al, 1992;Bostick et al, 2000;Entezari et al, 2001;Shahkhalili et al, 2001;Reid et al, 2002) except that reported by Denke et al (1993). Noting that this report suffers from weak points with regard to the number of participants, large amount of calcium supplemented and specific population investigated, more studies are still needed for a consistent conclusion.…”
Section: Discussionsupporting
confidence: 87%
“…(2001) report and further findings of others, (Karanja et al, 1987;Bell et al, 1992) although the observed elevation in TG was not significant. However, our finding contraindicates the results reported by Shahkhalili et al (2001). The observed hypertriglyceridemia in our trial is of importance as it carries risk for CHD (Krummel, 2004).…”
Section: Discussioncontrasting
confidence: 76%
See 2 more Smart Citations
“…One contributing factor is that dietary calcium increases soap formation in the gastrointestinal tract, making fat unavailable for absorption and reducing calorie intake. [17][18] Parikh and Yanovski 19 calculated that an extra 2000 mg calcium/day in a 2500 kcal/ day diet would bind enough lipid to account for a body weight loss of about 0.5 kg per year, which is equivalent to the weight difference that has been attributed to dietary calcium intake in the analysis by Davies et al 9 Similarly, increased fecal excretion of lipid accounted for all of the difference in body fat content of rats fed a high-calcium diet. 13 The impact of increased calcium intake during food restriction has not been evaluated but, theoretically, it could produce a proportionally greater energy deficit in low-calorie, low-fat diets.…”
mentioning
confidence: 99%